2022
DOI: 10.1172/jci.insight.162968
|View full text |Cite
|
Sign up to set email alerts
|

The effect of induction immunosuppression for kidney transplant on the latent HIV reservoir

Abstract: The HIV latent viral reservoir (LVR) remains a major challenge in the effort to find a cure for HIV. There is interest in lymphocyte-depleting agents, used in solid organ and bone marrow transplantation to reduce the LVR. This study evaluated the LVR and T cell receptor repertoire in HIV-infected kidney transplant recipients using intact proviral DNA assay and T cell receptor sequencing in patients receiving lymphocyte-depleting or lymphocyte-nondepleting immunosuppression induction therapy. CD4 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Studies have shown that kidney transplant patients who received lymphocyte nondepleting therapies had a slight reduction of CD4 + T-cell counts, and intact and defective provirus initially, but levels returned to baseline [ 5 ]. Liver transplant recipients in this study receiving lymphocyte nondepleting therapies show similar results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown that kidney transplant patients who received lymphocyte nondepleting therapies had a slight reduction of CD4 + T-cell counts, and intact and defective provirus initially, but levels returned to baseline [ 5 ]. Liver transplant recipients in this study receiving lymphocyte nondepleting therapies show similar results.…”
Section: Discussionmentioning
confidence: 99%
“…IPDA was performed as previously described (Accelevir Diagnostics) [ 5 ]. Briefly, total CD4 + T cells were isolated from cryopreserved PBMCs via immunomagnetic selection, and genomic DNA was isolated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations